2014
DOI: 10.4238/2014.june.17.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitochondrial ATP-sensitive potassium channel opening on the translocation of protein kinase C epsilon in adult rat ventricular myocytes

Abstract: ABSTRACT. This study aimed to investigate the effects of mitochondrial ATP-sensitive potassium (MitoK ATP ) channel opening on the translocation of protein kinase C epsilon (PKCε). In addition, we aimed to determine the relationship between PKCε translocation and the production of reactive oxygen species (ROS). PKCε protein expression in cultured adult rat ventricular myocytes was investigated by immunofluorescence and Western blotting. Diazoxide (DZ), a selective MitoK ATP channel activator, caused a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, NNC 55-0462, another novel potassium channel opener, does not promote εPKC activation [ 34 ]. In rat ventricular myocytes, diazoxide, a mitoK ATP channel opener, induces εPKC translocation [ 35 ]. εPKC inhibitor cheleryhrine does not abolish infarct size-limiting effect of diazoxide in rabbit hearts, but it blocks the protective effect of diazoxide in rat myocardial infarction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, NNC 55-0462, another novel potassium channel opener, does not promote εPKC activation [ 34 ]. In rat ventricular myocytes, diazoxide, a mitoK ATP channel opener, induces εPKC translocation [ 35 ]. εPKC inhibitor cheleryhrine does not abolish infarct size-limiting effect of diazoxide in rabbit hearts, but it blocks the protective effect of diazoxide in rat myocardial infarction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of myocytes, researchers observed that opening of mitoKATP channels may activate PKC ε and induce its translocation into myofibrillar-like structures. PKC ε activation occurs downstream of the mitoKATP channel, possibly as a result of ROS production after the opening of mitoKATP channels [ 30 ]. In the present study, we demonstrated that diazoxide can increase PKC ε expression but that this increase in expression is abrogated by 5-HD.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, both AT 1 R and AT 2 R lack a subcellular targeting sequence (2), and whether they are bound to molecular chaperones and TOM70 (38) remains unknown. A translocation process, however, is supported by the inhibitory effect of chelerythrine, which reportedly inhibits the activation/translocation of PKC from the cytosol to subcellular or particulate fractions (3,57).…”
Section: Mitochondrial Angiotensin Receptors and Cardioprotectionmentioning
confidence: 99%